A preliminary randomised controlled study of short-term Antrodia cinnamomea treatment combined with chemotherapy for patients with advanced cancer. Issue 1 (December 2016) - Tsai, Ming-Yen; Hung, Yu-Chiang; Chen, Yen-Hao; Chen, Yung-Hsiang; Huang, Yu-Chuen; Kao, Chao-Wei; Su, Yu-Li; Chiu, Hsien-Hsueh; Rau, Kun-Ming
Abstract Background Antrodia cinnamomea (AC) is a popular medicinal mushroom in Taiwan that has been widely used for treatment of various cancers. Few clinical studies have reported its application and efficiency in therapeutic chemotherapy strategies. We performed a double-blind, randomized clinical study to investigate whether AC given for 30 days had acceptable safety and efficacy in advanced cancer patients receiving chemotherapy. Methods Patients with advanced and/or metastatic adenocarcinoma, performance status (PS) 0–2, and adequate organ function who had previously been treated with standard chemotherapy were randomly assigned to receive routine chemotherapy regimens with AC (20 ml twice daily) orally for 30 days or placebo. The primary endpoint was 6-month overall survival (OS); the secondary endpoints were disease control rate (DCR), quality of life (QoL), adverse event (AE), and biochemical features within 30 days of treatment. Results From August 2010 to July 2012, 37 subjects with gastric, lung, liver, breast, and colorectal cancer (17 in the AC group, 20 in the placebo group) were enrolled in the study. Disease progression was the primary cause of death in 4 (33.3 %) AC and 8 (66.7 %) placebo recipients. Mean OSs were 5.4 months for the AC group and 5.0 months for the placebo group (p  = 0.340), and the DCRs were 41.2 and 55 %, respectively (p  = 0.33). Most hematologic, liver, or kidney functions did not differ significantly between the two groups, but platelet counts were lower in the AC group than in the placebo group (p  = 0.02). QoL assessments were similar in the two groups, except that the AC group showed significant improvements in quality of sleep (p  = 0.04). Conclusions Although we found a lower mortality rate and longer mean OS in the AC group than in the control group, A. cinnamomea combined with chemotherapy was not shown to improve the outcome of advanced cancer patients, possibly due to the small sample size. In fact, the combination may present a potential risk of lowered platelet counts. Adequately powered clinical trials will be necessary to address this question. Trial registration ClinicalTrials.govNCT01287286 .